SOAR Strategy Analysis to Increase The Competitiveness of Medan Supermarket Brastagi - Widya Rizky Amelia; Sugianto (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
There are three types of modern markets, namely minimarkets, supermarkets and hypermarkets. Brastagi Supermarket managed by PT. Jaya Anugrah Sukses Abadi is a type of supermarket in addition to other types of supermarkets operating in the city of Medan. So that requires Brastagi Supermarket to have an advantage in the competition. This study aims to analyze the competitiveness strategy of Berastagi Supermarkets in order to achieve competitive advantage among supermarkets in Medan City. This study uses a qualitative method with secondary data and document studies as a method of collecting data through books, journals and existing research. The data analysis used is SOAR analysis which pays attention to both internal and external environment by looking at the strengths, opportunities, aspirations and results obtained with the analysis. SOAR analysis requires companies to carry out activities effectively and efficiently in achieving their goals which are sourced from the many opportunities and aspirations created by always improving the quality and quantity of innovating products and to ensure customer satisfaction as the number one priority for Brastagi Supermarkets in order to be able to achieve excellence. in competitive advantage.